2019
DOI: 10.3390/v11050428
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Dependent Production of ROS and Restriction of HSV-1 Infection in U937 Monocytic Cells

Abstract: Herpes simplex virus 1 (HSV-1) can infect a wide range of cell types, including cells of the adaptive and innate immunity but, normally, it completes a fully-permissive replication cycle only in epithelial or neural cells. Complex mechanisms controlling this delicate balance in immune cells and consequent restriction of HSV-1 infection in these cells have not been completely elucidated. We have recently demonstrated that the transcription factor nuclear factor kappa B (NF-κB) can act as a main permissiveness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It was shown that HSV-1 infection quickly induced intracellular ROS that were necessary for proper activation of innate antiviral immune responses [37]. Initial generation of ROS post virus infection acts as a microbicidal compound to regulate several processes, such as expression of innate-response-related genes, NF-κB activation, inflammasome activation, autophagy and programmed necrosis [3840]. However, its overproduction may exacerbate downstream inflammatory responses as well as oxidative injury depending on the absolute intracellular levels of ROS and other reactive species [16, 41].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that HSV-1 infection quickly induced intracellular ROS that were necessary for proper activation of innate antiviral immune responses [37]. Initial generation of ROS post virus infection acts as a microbicidal compound to regulate several processes, such as expression of innate-response-related genes, NF-κB activation, inflammasome activation, autophagy and programmed necrosis [3840]. However, its overproduction may exacerbate downstream inflammatory responses as well as oxidative injury depending on the absolute intracellular levels of ROS and other reactive species [16, 41].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, NF-κB activation is one of the main mechanisms present in HSV-1-infected cells and is known to be closely related to ROS production [27]. Therefore, we checked whether the inhibition of NF-κB activation is also associated with ROS generation in QA-treated cells infected with HSV-1.…”
Section: Qa Induces Inhibition Of Ros Production By Hsv-1 Infection In Sk-n-sh Cellsmentioning
confidence: 95%
“…Despite possible antiviral effects of oxidative stress responses (49,50), we observed that ROS inhibition reduced DENV replication in HBMEC. Different mechanisms might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 59%